The Effect of Physical Exercise on Quality of Life of Breast Cancer Survivors: A Systematic Review - Jadmiko, Arief Wahyudi; Kristina, Tri Nur; Sujianto, Untung; Prajoko, Yan Wisnu; Dwiantoro, Luky; Widodo, Aris Puji (Indonesian Journal of Medicine, 2021)
Background: Exercise generally improves the quality of life (QoL) in adult populations especially for patients with chronic health problems such as breast cancer. The purpose of this study was to investigate the effect of physical exercise/activity on the quality of life of breast cancer survivors. Subjects and Method: This was a systematic review study that used articles from online databases, such as  PubMed, Science Direct, ProQuest dan Medline, which was published from 2000 to 2021. The author used keywords of “physical exercise”, “physical activity”, “quality of life”, “breast cancer survivor”. The dependent variable was quality of life. The independent variable was physical exercise/ activity. As many as 5 articles were selected for this study from 837 articles located in South Korea, Iran, Malaysia, and China.Results: Moderate or high levels of physical activity had positive relationship on the quality of life related to overall physical health among breast cancer survivors.Conclusion: Moderate to high physical activity improve the quality of life among breast cancer survivors.Keywords: physical exercise, physical activity, quality of life, breast cancer survivor Correspondence: Arief Wahyudi Jadmiko. Nursing Department, Faculty of Health, Universitas Pembangunan Nasional Veteran Jakarta. Jl. Raya Limo Depok 16515 West Java, Indonesia Email: ariefwjadmiko@gmail.com. Mobile: 085647213628. ORCID ID https://orcid.org/0000-0002-9691-0986.Indonesian Journal of Medicine (2021), 06(04): 377-386https://doi.org/10.26911/theijmed.2021.06.04.03